Reading the Footprints: How Foreign Investors Shape Countries' Participation in Global Value Chains. Issue 4 (December 2017) - Buelens, Christian; Tirpák, Marcel
Abstract Gravity variables play a significant role in explaining trade flows related to global value chain participation. We find evidence that cooperation costs – measured by linguistic and geographical proximity – are more relevant for trade that reflects cross-border production sharing compared to trade in final goods. Applying an augmented gravity model framework to a newly constructed dataset, we find a positive association between bilateral FDI stock and both gross bilateral trade and the bilateral import content of exports. As bilateral FDI stock affects both the volume and composition of trade flows, we conclude that foreign investors play an active role in shaping host economies' export structure and their participation in international production networks.